2021
DOI: 10.1177/19418744211035370
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Facial Focal Seizures With Chronic Striatopathy and Caudate Atrophy—A Double Whammy in an Elderly Woman With Diabetes Mellitus

Abstract: Seizures and involuntary movements are relatively rare, but well-known neurological complications of non-ketotic hyperglycemia. While hemichorea-hemiballism secondary to diabetic striatopathy is increasingly being reported, unilateral caudate atrophy resulting from chronic vascular insufficiency/insult in a backdrop of poorly controlled diabetes mellitus is sparsely described in literature. We herein report a 75-year-old woman with poorly controlled diabetes mellitus who presented with concurrent epilepsia par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Diabetic striatopathy, coined as an umbrella term, is defined as a hyperglycemic condition associated with both or either one of the two following conditions: (i) acute onset chorea-ballism and (ii) striatal hyperdensity on computed tomography (CT) or striatal hyperintensity on T1-weighted magnetic resonance imaging (MRI) [1][2][3][4][5][6][7][8][9][10][11][12]. Previous clinical series and systematic review regarding acute onset movement disorders in diabetes mellitus (DM) included only patients with chorea or ballism (Table 1) [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetic striatopathy, coined as an umbrella term, is defined as a hyperglycemic condition associated with both or either one of the two following conditions: (i) acute onset chorea-ballism and (ii) striatal hyperdensity on computed tomography (CT) or striatal hyperintensity on T1-weighted magnetic resonance imaging (MRI) [1][2][3][4][5][6][7][8][9][10][11][12]. Previous clinical series and systematic review regarding acute onset movement disorders in diabetes mellitus (DM) included only patients with chorea or ballism (Table 1) [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Non-ketotic hyperglycemia, unilateral limb choreographic dyskinesia, and striatal abnormalities on neuroimaging are typical signs of DS. Previous studies have found that chorea associated with hyperglycemia occurs mostly unilaterally and rarely bilaterally; a few may occur in hypoglycemic states or after correction of hyperglycemia [ 1 , 16 18 ], and a few DS cases reported no chorea [ 18 20 ] or had nonchoreic and nonballistic movements [ 7 , 12 , 14 , 18 , 21 , 22 ]. The imaging manifestation may also be unremarkable [ 16 , 18 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite its normal MRI appearance, its function was impaired [ 25 ], which may be one of the reasons why there is no obvious correlation between the differences in imaging findings and the severity and duration of chorea in DS patients. Although DS is a reversible disease, in the study of Ghosh et al [ 21 ], the striatum on the affected side was atrophied without abnormal signal, which indicates the diversity of imaging findings of DS; it is suggested that striatal atrophy may be the final trend of imaging abnormalities in DS, especially those without active treatment [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with DS usually have a good prognosis with complete amelioration after correction of the hyperglycemia. A few patients developed persistent chorea even under a backdrop of well-controlled diabetes mellitus or complete resolution of abnormal striatum signals, suggesting the presence of irreversible damage (Ahlskog et al, 2001 ; Wu et al, 2014 ; Roy et al, 2016 ; Lucassen et al, 2017 ; Chatterjee et al, 2022 ). Severe or uncontrolled hyperglycemia is associated with chorea relapse and the attacks of acute cerebrovascular events, such as acute cerebral infarction and hemorrhage, leading to a poor prognosis (Carrion and Carrion, 2013 ; Lucassen et al, 2017 ; Chua et al, 2020 ; Dong and Zhang, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the imaging presentations of DS are generally reversible in most patients, irreversible striatum lesions, such as caudate atrophy, have been occasionally reported in previous reports (Lucassen et al, 2017;Chatterjee et al, 2022). Longterm uncontrolled hyperglycemia is a major cause of irreversible striatal damage (Lucassen et al, 2017;Chatterjee et al, 2022).…”
Section: Imaging Featuresmentioning
confidence: 98%